The merry adventures of Robin Hood - Pyle, Howard 1853-1911.; Kestel, Deborah; Pablo Marcos Studio (New York Baronet Books, 1990)
Recounts the legend of Robin Hood, who plundered the king's purse and poached his deer and whose generosity endeared him to the poor.
Keywords: Robin Hood (Legendary character) -- Legends; Robin Hood (Legendary character) -- Legends; Folklore -- England